Highly Efficient Spectrally Stable Red Perovskite Light‐Emitting Diodes. Issue 20 (30th March 2018) - Tian, Yu; Zhou, Chenkun; Worku, Michael; Wang, Xi; Ling, Yichuan; Gao, Hanwei; Zhou, Yan; Miao, Yu; Guan, Jingjiao; Ma, Biwu
Abstract: Perovskite light‐emitting diodes (LEDs) have recently attracted great research interest for their narrow emissions and solution processability. Remarkable progress has been achieved in green perovskite LEDs in recent years, but not blue or red ones. Here, highly efficient and spectrally stable red perovskite LEDs with quasi‐2D perovskite/poly(ethylene oxide) (PEO) composite thin films as the light‐emitting layer are reported. By controlling the molar ratios of organic salt (benzylammonium iodide) to inorganic salts (cesium iodide and lead iodide), luminescent quasi‐2D perovskite thin films are obtained with tunable emission colors from red to deep red. The perovskite/polymer composite approach enables quasi‐2D perovskite/PEO composite thin films to possess much higher photoluminescence quantum efficiencies and smoothness than their neat quasi‐2D perovskite counterparts. Electrically driven LEDs with emissions peaked at 638, 664, 680, and 690 nm have been fabricated to exhibit high brightness and external quantum efficiencies (EQEs). For instance, the perovskite LED with an emission peaked at 680 nm exhibits a brightness of 1392 cd m −2 and an EQE of 6.23%. Moreover, exceptional electroluminescence spectral stability under continuous device operation has been achieved for these red perovskite LEDs. Abstract : Highly efficient red‐emitting light‐emitting diodes based on quasi‐2D perovskite/polymer composite thin films are demonstrated. They are shown to have maximal brightness of 1392 cd m −2 and external quantum efficiencies of 6.23%.